The impact of echocardiographic parameter ratio of E/E' on the late recurrence paroxysmal atrial fibrillation in patients accepted radiofrequency catheter ablation: A retrospective clinical study. Issue 17 (April 2020) - Gong, Ke-Zeng; Yan, Qin-Dan; Huang, Rong-Da; Chen, Jian-Hua; Chen, Xue-Hai; Wang, Wei-Wei; Xu, Zhe; Chen, Liang-Long; Fan, Lin; Zhang, Fei-Long
Abstract : Abstract: This study aimed to evaluate the impact of the echocardiographic parameter ratio E/E' on the late recurrence of paroxysmal atrial fibrillation in patients after receiving radiofrequency catheter ablation. We retrospectively examined total of 288 paroxysmal atrial fibrillation (PAF) patients that underwent a preliminary radiofrequency catheter ablation (RFCA) in our hospital. During the first phase in this study, the patients were divided into 2 groups upon AF recurrence after RFCA: Recurrent group, n = 67 patients with rapid trial arrhythmia that lasted for more than 30 seconds at 3 months after RFCA and the Nonrecurrent group, n = 221. The clinical conditions were compared between the 2 groups. During the second phase of this study, based on the results in the first phase, the patients were divided into another 2 groups according to whether the ratio of E/E' ≥13 .45: Higher ratio of E/E' group, n = 55 and Lower ratio of E/E' group n = 233. The late AF recurrent rates were also compared between the 2 groups. During the first phase, the univariate analysis indicated that the risk factors( P  < .05)for PAF late recurrence included early recurrence, E', and the ratio E/E'. The Cox multivariate analysis showed that the ratio of E/E' and early recurrence were the independent predictors for late PAF recurrence. The ratio of E/E' that was cut off at 13.45 also predicted atrial tachyarrhythmia recurrence with 40.3% sensitivity and 87.3% specificity. In the second phase, after completing the 1:1 matching, the Kaplan–Meier analysis indicated that the ratio of E/E' ≥ 13.45 was associated with further recurrences after RFCA (log-rank P  = .009), compared to the patients with a ratio of E/E' < 13.45. The univariate Cox analysis indicated that an elevated ratio of E/E'(≥13.45) was the independent predictor for late PAF recurrence (HR = 3.322, 95%CI: 1.560–7.075, P  = .002). However, the ratio of E/E' cut off at 13.25 predicted atrial tachyarrhythmia recurrence with 75% sensitivity and 62.2% specificity. The ratio of E/E' ≥ 13.25 is an important predictor of the late recurrence of paroxysmal atrial fibrillation (PAF) after radiofrequency catheter ablation (RFCA).